The relationship of aerobic and anaerobic indices to middle distance running performance - Sleivert, G. G.; Reid, A. K. (Medicine & Science in Sports & Exercise, 1996)
The relationships of laboratory and field measures to middle-distance running performance were assessed. Tests traditionally used for long distance runners (VO2peak, LT, and running economy) may also be used for middle-distance runners. Time-trial information was at least as useful as laboratory tests for monitoring and predicting middle-distance running performances. Implication. Time-trial information is as useful as laboratory tests for monitoring training progress and status of middle-distance runners. At best, laboratory tests can be used to verify that which can be deduced from time-trial performances.